A descentralização da Política de Atenção ao HIV/AIDS no SUS-Sistema Único de Saúde: estudo comparativo das ações entre Rio Grande do Sul e Pernambuco - Jardim, Luciane Pinheiro (Universidade do Vale do Rio dos Sinos, 2018)
The present proposal of doctoral thesis aims by means of a comparative study to understand how the state governments of Rio Grande do Sul and Pernambuco; the municipal governments of Porto Alegre and Recife (representedby managers ofstateand municipal STD / HIV / AIDS programsandhealthprofessionals); and in thesameway, therepresentativesofthe Social MovementofFightagainst AIDS - NGO / AIDS Forum / RS andArticulationAIDS/PE; perceive the conditions of effectiveness of the proposal of change, in the model of specialized attention to HIV/AIDS, for the Basic Attention Service. For this study, a qualitative research was conducted in the field of Social Sciences, through a comparative study, in which the methodological procedures used were: semi-structured interview, documentary analysis, field diary and participant observation, and as analysis technique A qualitative comparative analysis was performed. From the data collected, it was verified that the Ministry of Health's proposal for decentralization of HIV for Basic Care is in progress in the state of Rio Grande do Sul and Porto Alegre, although there are limitations, while in Pernambuco and Recife the process was not implemented due to the fragility of Primary Care services. However, it is considered that for the implementation or maintenance of this strategy of sharing care, there should be, beyond the political and managerial will, the funding to foster the necessary actions, as well as the granting of universal access rights to health services.
Keywords: Política pública; Política de HIV/AIDS; Descentralização; Public policy; HIV/AIDS policy; Decentralization; ACCNPQ::Ciências Humanas::Sociologia